The Art of Erasure: Jean-Michel Basquiat’s Olympias - Cristian, Réka M. (Hungarian Journal of English and American Studies, 2020)
This essay discusses the visual shift of race and gender representation in a selection of Jean-Michel Basquiat’s paintings. The Brooklyn graffiti artist, who was known for elevating the street energy of vernacular inscriptions into high art, reinterpreted Édouard Manet’s Olympia (1863) in Three-Quarters of Olympia Minus the Servant (1982) by erasing racial difference and challenging gender stereotypes in a work devoid of gender markers. In Untitled (Maid from Olympia) (1982), another version of the modernist painting, Basquiat places the figure of the black servant, formerly a colonized subject, in the center of the work; as a result, the servant “talks back” in a visual narrative functioning as a critique of colonization. Both paintings thus recast and reinterpret Manet’s Olympia and her world in a contemporary signification of race and gender by emphasis, or lack thereof, of such markers. (RMC)